A systematic review of the impact of inflammatory bowel disease (IBD) on family members. Issue 9 (31st July 2022) - Thapwong, Parichat; Norton, Christine; Rowland, Emma; Farah, Noora; Czuber‐Dochan, Wladyslawa
Abstract: Background and Aims: Inflammatory Bowel Disease (IBD) affects patients and their family members, but most reviews have focused only on patients themselves. This review synthesises evidence on the impact of IBD on family members. Methods: A systematic review was undertaken, searching six bibliographic databases, focusing on the impact of IBD on family members, coping strategies, and interventions. A narrative synthesis was conducted. This review was reported following the Preferred Reporting Items for Systematic Reviews (PRISMA). Results: 3258 records were identified; 33 papers (2748 participants) were included. Three themes were identified: impact of IBD on family members; coping strategies for family members to overcome the impact of IBD; and the support needed by family members. IBD affects family members' well‐being in many ways, including their emotional well‐being, relationship with the patient, social life, work and finances, and leisure time and travel. Family members use adaptive coping patterns such as acceptance, developing resilience, and emotional support from others. Maladaptive coping patterns such as denial of diagnosis, self‐distraction, and self‐blame were also evident. Family members reported that they needed better information about IBD, support groups, and better access to a counsellor or psychologist. No studies assessed interventions to relieve family members' burden. Conclusions: Family members of IBD patients require psychosocial support to facilitate better family function, cohesion, and enhanced coping strategies. Healthcare services should adopt a multidisciplinary care model with a bio‐psycho‐social approach including an IBD nurse, family therapist, and psychologist, to improve quality of life for patients and their families.